Construção e aplicação analítica de eletrodos de pasta de carbono modificada com ftalocianina de cobalto para determinação de analítos de interesse - Conceição, Cleone das Dores Campos (2004)
In this thesis work the development and applications of cobalt phthalocyanine carbon paste electrode (CoPc/CPE) for voltammetric determination (cyclic voltammetry and differential pulse voltammetry) of hydrazine in boiler feed water, dopamine, vitamin B1 (thiamine) and vitamin B6 (pyridoxine) in pharmaceutical preparations available commercially in the market, without any previous treatment of the samples. The CoPc/CPE presented voltammetric response (for cyclic voltammetry and differential pulse voltammetry) linear in the hydrazine concentration range from 1,3x10-4 to 9,8x10-4 mol L-1, with detection limit of 3,0x10-5 mol L-1 and 5,0x10-5 to 7,4x10-4 mol L-1, with detection limit of 2,3x10-5 mol L-5, respectively. The hydrazine quantification in waters of boilers using CoPc/CPE presented results of agreement with the spectrophotometric method with an interval of acceptable relative error. The CoPc/CPE presented a voltammetric response (for cyclic voltammetry and differential pulse voltammetry) linear in the dopamine concentration range from 1,3x10-5 to 2,8x10-4 mol L-1, with detection limit of 1,0x10-5 mol L-1e 5,0x10-6 to 9,8x10-5 mol L-1, with limit of detection of 1,4x10-6 mol L-1, respectively. That modified electrode presented good performance as voltammetric sensor in the dopamina determination in pharmaceutical preparations. The CoPc/CPE presented an voltammetric response (differential pulse voltammetry) linear in the vitamin B1 (thiamine) concentration range from 5,0x10-5 to 3,8x10-4 mol L-1, with detection limit of 2,5x10-5 mol L-1. The thiamine quantification in pharmaceutical formulations using CoPc/CPE presented results of agreement with the spectrofluorimetric method of Brazilian Pharmacopeia s with an interval of acceptable relative error. CoPc/CPE presented an voltammetric response (for cyclic voltammetry and differential pulse voltammetry) linear in the vitamin B6 (pyridoxine) concentration range from 5,0x10-5 to 9,8x10-4 mol L-1, with detection limit of 4,7x10-6 mol L-1 and 5,0x10-5 to 3,4x10-4 mol L-1, with detection limit of 1,3x10-6 mol L-1, respectively. That modified electrode presented good performance as voltammetric sensor in the pyridoxine determination in pharmaceutical preparations. The CoPc/CPE was also used in the simultaneous determination of vitamins B1 (thiamine) and B6 (pyridoxine) by differential pulse voltammetry, in pharmaceutical preparations, once the oxidation peaks potentials of the vitamin B1 (-0,13 V) and vitamin B6 (0,55V), healthy very different. The analytic curves were linear in the interval of thiamine concentration of 1,9x10-4 to 7,4x10-4 mol L-1, with limit of detection of 8,4x10-5 mol L-1 and of 1,0x10-4 to 7,4x10-4 mol L-1, with limit of detection of 1,5x10-5 mol L-1 for pyridoxine. That modified electrode presented satisfactory acting as voltammetric in the determination of both in pharmaceutical preparations.